SIMULATION OF REMOTE AND INTELLIGENT SUPERVISION VIA “INTERNET OF THINGS (IoT)” OF A SYSTEM FOR WATER SUPPLY IN CIVIL BUILDINGS USING LIFT MOTOR PUMPS - Stehling Ferreira Silva, Danilo (2024)
Water is an essential input for the maintenance of life, its supply is carried out by lifting motor pumps. Equipment that is subject to stress and failures arising from several factors, one of them is the occurrence of cavitation in the pump rotors that subject the material of this equipment to erosive wear that occurs through micro implosions of steam bubbles. This work presents the architecture and simulation of the operation of the embedded system that was developed for the activation and supervision of the use of two motor pumps, applied to the water supply in civil buildings. The motor pumps are activated in alternating mode to supply the supply demand, and the pump operating temperature is monitored for the application of a fuzzy diagnostic system regarding the tendency for cavitation to occur. The entire operation of the supply system can be monitored using a mobile application processed by smartphone, developed on the Android platform. The tests carried out for different modes of operation, as well as the diagnosis and signaling of the pump's heating condition, proved the validity of the proposal.